Correlation and regression analysis of yield components between F3 and F4 genera- tions in fenugreek (Trigonella foenum-graecum L.) - R S Raje, M K Yadav, (Journal of Spices and Aromatic Crops, 2017)
Evaluation of 21 F4 progeny families and the corresponding F3 parent families of fenugreek(Trigonella foenum-graecum) at Jobner (Rajasthan) indicated that the value of rop (correlationbetween offspring and parents) and bop (regression of offspring on parents) were low forprimary branches plant-1, when primary branches plant-1 was taken as selection criterion.Low rop and bop values were also recorded for pods plant-1 and seeds pod-1 when pods plant-1and seeds pod-1 were taken as selection criterion. Whereas, highly significant rop and bopvalues were recorded for other parameters that were not taken as selection criterion for eachof the three traits namely, pods plant-1, primary branches plant-1 and seeds pod-1. This indicatedthat there was more resemblance between parents and offsprings for these characters andselection did not have much effect on these characters.